The comedy of errors simplified: ‘Egeon’s 18th reasons why’ / Nurul Atikah Mohamad Akmal Paramswhren and Chong Oi Leng - Mohamad Akmal Paramswhren, Nurul Atikah; Oi Leng, Chong (Academy of Language Studies, 2023)
Published in 1594, The Comedy of Errors is one of William Shakespeare's early plays. Recounting the tale of two sets of identical twins who have unexpectedly split apart following an incident. This is one of his shortest and most bizarre comedies, with a large portion of the humour coming from slapstick and puns. This project attempts to produce a fresh approach to reading and comprehending great literature. Additionally, The Comedy of Errors Simplified: Egeon's 18th Reasons Why, an educational e-book innovation, is proposed as part of this project as a means of encouraging general audiences, particularly non-readers and second language learners, to acquire and become familiar with numerous literary classics. As the title implies, this project will take classics that are today referred to as "too long didn't read" (TLDR) and transform them into something more exciting and more straightforward for everyone to enjoy. The study's conclusions showed that including the modern English language and comical arts in literature, learning generated favourable responses from the intended audience and helped spark their interest in the subject.